Prevention program for sexually transmitted infections and HIV/AIDS: An experience from Bahia - Pamponet de Oliveira, Leonardo; Patel, Balmukund Niljay (Guará Journal, 2025)
The Sexually Transmitted Infections and HIV/AIDS Prevention Program (UEFS) emerged as a tool to promote the prevention of sexually transmitted infections and HIV/AIDS within the academic community of the State University of Feira de Santana. Initially, the Program provided training sessions in the form of mini-lectures for students at events hosted by the University itself. The speakers' approaches varied across the various age groups, resulting in positive response and engagement among the target population, who participated in the various health promotion and prevention events for sexually transmitted infections, especially AIDS.
Keywords: Program; Prevention; HIV, Aids